Concerns regarding hair cortisol as a biomarker of chronic stress in exercise and sport science - Gerber, M.; Brand, S.; Lindwall, M.; Elliot, C.; Kalak, N.; Herrmann, C.; Pühse, U.; Jonsdottir, I. H. (Journal of Sports Science & Medicine, 2012)
Hair cortisol has the potential to fill the methodological void of long-term cortisol assessment while becoming a widely accepted measure in biopsychology. This review critically examines the applicability and relevance of hair cortisol measurement specifically within the field of exercise and sport science. Current measures of the HPA axis only cover a brief time period, whereas hair cortisol is a unique, non-invasive means to capture long- term cortisol secretion. Studies have shown that individuals who have elevated cortisol secretion (e.g. due to diseases associated with a disturbed activation of the HPA axis or exposure to stressful life events) reveal increased hair cortisol. By contrast, only weak correlations exist between hair cortisol and perceived stress, and the direction of the relationship between hair cortisol levels and mental disorders is unclear. Acute exercise, however, results in increased levels of cortisol that eventually is reflected in higher levels of cortisol in hair samples and studies have shown that exercise intensity is related to hair cortisol level. Thus, elevated hair cortisol levels found among regular exercisers are not necessarily pathological. Thus, one should practice caution when associating athletes' elevated hair cortisol with poor mental health or disease. Hair cortisol analysis can contribute to a more complete understanding of how long-term cortisol elevation mediates stress-related effects on the health and performance of recreational exercisers and elite athletes. Nevertheless, it is crucial for exercise and sport scientists to consider whether their research questions can be adequately addressed, given that regular intense exercise results in substantially augmented hair cortisol levels.